Migration patterns and access to reproductive and maternal healthcare among women aged 15–49 years in Ghana: insights from a population-based national survey - Dadras, Omid; Osborne, Augustus; Wongnaah, Florence Gyembuzie; Seidu, Abdul-Aziz; Ahinkorah, Bright Opoku (Springer Science and Business Media LLC, 2025)
Background
Maternal health remains a critical public health concern in Ghana, with significant disparities in healthcare access between rural and urban areas. Women in rural regions face a higher risk of maternal mortality, preterm births, and pregnancy complications due to limited health care services. Migration patterns further exacerbate these issues by disrupting access to essential reproductive and maternal services. While some women travel specifically for medical care and later returned, others migrate due to family-related reasons.This study investigates the association between migration patterns and access to reproductive and maternal healthcare services among Ghanaian women aged 15–49.
Methods
Data from the 2022 Ghana Demographic Health Survey was used for this study. Bivariate and multivariable logistic regression models were used to investigate the association between migration patterns and access to reproductive and maternal healthcare services.
Results
There was no significant association between the migration stream and unmet family planning needs in both unadjusted and adjusted logistic models. The odds of adequate antenatal care were higher among rural to urban, urban to urban, and urban non-migrants than rural non-migrants. In the adjusted model, however, it only remained significant for rural to urban migrants. The odds of institutional delivery were significantly higher among rural to urban and urban to rural migrants than rural non-migrants. However, in the adjusted model, the odds of institutional delivery only remained significant for urban to urban, rural to urban, and urban non-migrants.
Conclusion
Migration patterns are associated with access to reproductive and maternity healthcare in Ghana. Women who migrate from urban to urban areas experience the most significant improvement in accessing antenatal care and institutional delivery services. Regardless of migration history, urban residents have better access than rural non-migrants. To improve maternal healthcare, the government should enhance rural healthcare infrastructure and staffing, support rural to urban migrants in navigating urban healthcare, and implement comprehensive maternity education campaigns for all women.